Non-Invasive Diagnosis for Acute Rejection Using Urinary mRNA Signature Reflecting Allograft Status in Kidney Transplantation - Seo, Jung-Woo; Lee, Yu Ho; Tae, Dong Hyun; Park, Seon Hwa; Moon, Ju-Young; Jeong, Kyung Hwan; Kim, Chan-Duck; Chung, Byung Ha; Park, Jae Berm; Kim, Yeong Hoon; Seok, Junhee; Joo, Sun Hyung; et al. (Frontiers in Immunology, 2021)
Urine has been regarded as a good resource based on the assumption that urine can directly reflect the state of the allograft or ongoing injury in kidney transplantation. Previous studies, suggesting the usefulness of urinary mRNA as a biomarker of acute rejection, imply that urinary mRNA mirrors the transcriptional activity of the kidneys. We selected 14 data-driven candidate genes through a meta-analysis and absolutely measured the candidate genes using quantitative PCR without pre-amplification in the cross-sectional specimens from Korean kidney transplant patients. Expression of 9/14 genes (CXCL9, CD3ε, IP-10, LCK, C1QB, PSMB9, Tim-3, Foxp3, and FAM26F) were significantly different between acute rejection and stable graft function with normal pathology and long-term graft survival in 103 training samples. Also, CXCL9 was distinctly expressed in allografts with acute rejection in in situ hybridization analysis. This result, consistent with the qPCR result, implies that urinary mRNA could reflect the magnitude of allograft injury. We developed AR prediction model with the urinary mRNAs by a binary logistic regression and the AUC of the model was 0.89 in the training set. The model was validated in 391 independent samples, and the AUC value yielded 0.84 with a fixed manner. In addition, the decision curve analysis indicated a range of reasonable threshold probabilities for biopsy. Therefore, we suggest the urine mRNA signature could be used as a non-invasive monitoring tool of acute rejection for clinical application and could help determine whether to perform a biopsy in a recipient with increased creatinine.